4x*-12x-45=0

Simple and best practice solution for 4x*-12x-45=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x*-12x-45=0 equation:


Simplifying
4x * -12x + -45 = 0

Reorder the terms for easier multiplication:
4 * -12x * x + -45 = 0

Multiply 4 * -12
-48x * x + -45 = 0

Multiply x * x
-48x2 + -45 = 0

Reorder the terms:
-45 + -48x2 = 0

Solving
-45 + -48x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + -48x2 = 0 + 45

Combine like terms: -45 + 45 = 0
0 + -48x2 = 0 + 45
-48x2 = 0 + 45

Combine like terms: 0 + 45 = 45
-48x2 = 45

Divide each side by '-48'.
x2 = -0.9375

Simplifying
x2 = -0.9375

Reorder the terms:
0.9375 + x2 = -0.9375 + 0.9375

Combine like terms: -0.9375 + 0.9375 = 0.0000
0.9375 + x2 = 0.0000

The solution to this equation could not be determined.

See similar equations:

| X+43=92 | | 2/4ex^-8 | | a^3+216b^3= | | x^2-y=100 | | f(x)=7log(x+1) | | y=-2x+200 | | 2x/8=8 | | x=cos(2y+p) | | 5sqrt(2)+2sqrt(2)= | | (x-5)/90 | | 4(x-4)=(x-26) | | 6x/8=-18 | | 5(x+6)=4x+3 | | -5=26w | | -7u=-22 | | 57=-y/4 | | 2/(3-2x)=1 | | x=y^2+7y+c | | 0=-x^2-6x-3 | | 8=x+(x+92) | | I=P(r+nt) | | 5x+2x=1260 | | 5(x+2)+12=-24 | | 5x-3/9 | | 3x-7+9-2x=28 | | (3+i)z^2+(5-5i)z+(-2+16i)=0 | | 2/3x-25=-29 | | 4x+3y=2x-6y | | (1+x^2)dy=(1+xy)dx | | 7y-12=4y+2 | | X^2+100x-15000=0 | | 9z-6-5z=-14 |

Equations solver categories